Ketuhanan dalam Era Pluralisme : Relevansi Sila Pertama Pancasila dalam Kebijakan Negara - Hamdan, Nur; Masyitoh, Siti (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to examine the relevance of the first principle of Pancasila in supporting diversity and the role of the state in maintaining harmony of diversity in Indonesia. The method used is a qualitative approach with a descriptive-analytical method. Based on the results of the analysis, it can be concluded that the First Principle,